KNOWLEDGE IMPROVEMENT: THE PERSPECTIVE OF CREDIT UNION SAUAN SIBARRUNG (CUSS) TANA TORAJA - Yohanny Yenny Salurerung; Marselinus Asri; Oktavianus Pasoloran (Faculty of Economics dan Business, Atma Jaya Makassar University, 2023)
The aim of research is to test the effect of Knowledge Improvement on Corperate Performance. Using respondent data at Credit Union Sauan Sibarrung with method data collection through questionnaire for 2020 period found results study about the influence of Knowledge Improvement. Knowledge Improvement effect in a manner positive and significant on Cooperative Performance. So this means diverse and continuous education and training provided to stakeholders, then will performance also increases credit union cooperative. Participation Member influential in a manner significant on Cooperative Performance. This mean the more good participation member to cooperative, then will the more good performance too cooperative There is influence significant between Knowledge Improvement and Participation Member in a manner together to the Cooperative Performance Credit Union seen F test results can seen from score Fcount on the ANOVA table Then could make conclusion, that the more sustainable education and training to member regarding its importance cooperate and the benefits that will obtained by members, by automatic participation member will increases, then will live influence performance cooperative.